Evaluating UMP Examination Timetable - M. N. M., Kahar; Shing, L. C. (American Scientific Publisher, 2018)
This work presents a study of examination timetabling problem from Universiti Malaysia Pahang (UMP). UMP operated from two campuses (i.e., Gambang and Pekan) and this formed new constraints for consideration in producing quality UMP examination timetable. These new constraints include schedule exams into appropriate campus and similar exams held in different campus must be assigned to the same timeslot. These constraints have not been examined before in the literature. UMP unable to evaluate examination timetable quality due to having no formal mathematical model. Hence, this paper aims to investigate the UMP examination timetabling constraints by developing a formal mathematical model and evaluate the current UMP examination timetable using the proposed formal mathematical model.